The Effect of High Loading Rate on the Behaviour and Mechanical Properties of Coal-Rock Combined Body - Fengqiang Gong; Hao Ye; Yong Luo (Shock and Vibration)
In order to investigate the high loading rate effect on the behaviour and mechanical properties of coal-rock combined body, the dynamic compressive tests were conducted by using the Split-Hopkinson Pressure Bar (SHPB) device under the loading rate range from 2.7×105 MPa/s to 4.0×105 MPa/s. The stress-strain curves, dynamic peak stress and strain, elastic modulus, and energy distribution law of coal-rock combined body under different loading rates were analyzed and discussed. The results show that the dynamic stress-strain curves of coal-rock combined body have a double-peak feature under high loading rate range, which can be divided into the initial bearing stage, the bearing decline stage, the bearing enhance stage, and the unstable stage. The first peak stress of the coal-rock combined body is independent of the loading rate, while the dynamic compressive strength (the second peak stress) and dynamic peak strain (the second peak strain) have a strong loading rate effect and will generally increase linearly with the loading rate. The first and second elastic moduli of coal-rock combined body are not sensitive to the loading rate. With the increase of the loading rate, the incident energy and reflective energy of coal-rock combined body increase rapidly, while the change of transmitted energy is very small. The absorption energy ratio of the coal-rock combined body shows a good linear law with the incident energy under different loading rates.